Association Analysis of MET Gene Polymorphism with Papillary Thyroid Carcinoma in a Chinese Population - Lifeng Ning; Yaqin Yu; Xiaoli Liu; Lizhe Ai; Xin Zhang; Wenwang Rao; Jieping Shi; Hui Sun; Qiong Yu (International Journal of Endocrinology)
To investigate the association of MET SNPs with gender disparity in thyroid tumors, as well as the metastasis and prognosis of patients, 858 patients with papillary thyroid carcinoma (PTC), 556 patients with nodular goiter, and 896 population-based normal controls were recruited. The genotyping of MET SNPs was carried out using the Sequenom MassARRAY system. The distribution of MET SNPs (rs1621 and rs6566) was different among groups. Gender stratification analysis revealed a significant association between the rs1621 genotype and PTC in female patients (P=0.037), but not in male patients (P>0.05). For female patients, the rs1621 AG genotype was significantly higher in patients with PTC than in normal controls (P=0.01) and revealed an increasing risk of PTC (OR: 1.465, 95% CI: 1.118–1.92). However, association analysis of the rs1621 genotype with metastasis and prognosis revealed no significant correlation in both male and female patients. The findings of our study showed that polymorphism of SNP locus rs1621 in MET gene may be associated with gender disparity in PTC. Higher AG genotypes in rs1621 were correlated with PTC in female patients, but not in male patients.